Stress and anxiety among late adulthood in Indonesia during COVID-19 outbreak - Ifdil, Ifdil; Yuca, Verlanda; Yendi, Frischa Meivilona (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2020)
This study analyzes the condition of stress and anxiety in late adulthood in Indonesia during the COVID-19 pandemic based on demographics. The research used quantitative methods with an online survey by survey monkey program involved 669 respondents based on twelve ethnicities in Indonesia. The data of this research analysis by the Rasch analysis model. The results showed generally experienced stress and anxiety in the moderate category although some respondents also experienced stress and anxiety in mild and severe categories, and only a small proportion was in the normal category. The need for continued treatment requires counselors, psychologists, and other relevant therapists.